Group work training for mental health professionals working with Syrian refugee children in Turkey: a needs assessment study - Sualp, K.; Ergüney Okumus, F.E.; Molina, O. (Routledge, 2021)
This study employed a grounded theory approach to understand group work training for mental health professionals (MHPs) working with Syrian refugee children in Turkey. Specifically, the authors set out to discover the barriers that prevent MHPs from conducting effective group work, elaborate on needed content and structure of the groups, highlight their potential benefits, and provide recommendations for conducting more effective group work to mitigate traumatic symptoms of Syrian refugee children. Interviews were conducted with 10 MHPs, including social workers (n = 4), psychologists (n = 5) and a psychiatrist (n = 1). Results revealed three themes including, i) Barriers for group work, ii) Benefits of group work, and iii) Recommendations for group work. Barriers included issues related to culture and language, access, intervention, organization and system-related barriers, and barriers stemming from ongoing trauma and abuse of Syrian refugee children, as well as secondary trauma of MHPs providing services. Benefits included MHPs’ perceived personal and interpersonal development skills, trauma resilience, and adjustment and adaptation for Syrian refugee children. Recommendations to mitigate the barriers for group work included the necessity of short term, cost-effective, ongoing crisis interventions that address stabilization and regulation of refugee children’s functioning. The study highlighted the importance of the effectiveness of interventions linked to qualifications of MHPs, designing group interventions that target the secondary trauma of MHPs, and the importance of psychosocial awareness interventions that aim to increase knowledge about refugee rights. © 2021 Taylor & Francis Group, LLC.
Keywords: Group work barriers; group work need; recommendations; refugee children; secondary trauma